1992
DOI: 10.1007/bf03167762
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of case retrieval times: Film versus picture archiving and communications systems

Abstract: One of the advantages that a picture archiving and communications system (PACS) is supposed to provide over a film-based operation is improved performance in retrieving images. Although it seems selfevident that this should be so, this experiment was intended to verify this and to provide some time comparisons for the two methods. The experiment consisted of randomly selecting ultrasound and computed tomography cases and determining how Iong it took to retrieve files at a PACS workstation or in person from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The exponential decay in report age is similar to the decline in the recall rate of prior exams from long-term storage described in the literature. 3,4,6 In addition to usage, system performance was also monitored. Figure 6 plots the throughput, as measured in number of studies per second returned, of both the PACS and RIS queries.…”
Section: Resultsmentioning
confidence: 99%
“…The exponential decay in report age is similar to the decline in the recall rate of prior exams from long-term storage described in the literature. 3,4,6 In addition to usage, system performance was also monitored. Figure 6 plots the throughput, as measured in number of studies per second returned, of both the PACS and RIS queries.…”
Section: Resultsmentioning
confidence: 99%
“…Because a PACS eliminates workload by reducing the number of hard-copy films produced (also saving money), is as reliable as a hard-copy environment, and decreases the number of lost film images, it has found a high acceptance rate in radiology departments (5,11,12). Several studies (1,5,11,(13)(14)(15)(16)(17) have shown an apparent reduction in the time of image delivery to the radiologist, retrieval of images, interpretation, and total report turnaround with use of a PACS. Integration of a PACS into the hospital information system and RIS has an additional positive impact on report turnaround time and communication between physicians (18 -20).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,18 Biaya dan inefisiensi penyimpanan gambar dalam PACS pernah dianggap sebagai hambatan untuk bergerak menuju pencitraan digital. 19 Tren dalam teknologi penyimpanan telah menunjukkan penurunan biaya media penyimpanan digital dan peningkatan kapasitas penyimpanan, sedangkan perangkat penyimpanan analog seperti kertas dan film hanya sedikit berubah atau bahkan mengalami peningkatan biaya. 20 Pengarsipan gambar digital dapat lebih efisien daripada penyimpanan data manual di ruang arsip film tradisional.…”
Section: Sistem Pengarsipanunclassified